E-LITIGASI DALAM MEWUJUDKAN ASAS PERADILAN SEDERHANA, CEPAT DAN BIAYA RINGAN - Fatin Hamamah (Mahkamah : Jurnal Kajian Hukum Islam, 2022)
The existence of electronic litigation services (e-litigation) is applied in all district courts in Indonesia. Regarding the use of e-litigation applied in court, the author will raise e-litigation as a research theme because there are still many people who do not understand the procedure for e-litigation. The method used in this study is a qualitative research method with an empirical juridical approach to examine the implementation of e-litigation in realizing the principle of simple, fast and low cost, with the research locus at the Majalengka District Court. The results showed that the implementation of e-litigation in realizing the principle of simple, fast and low-cost justice has not run optimally. There are several factors that become obstacles in the implementation of e-litigation, including disagreements from one party when conducting an e-litigation trial, people do not understand the use of technology and many people do not know about e-litigation (electronic trial).